KEMAMPUAN KEMANDIRIAN SISWA DALAM PELAJARAN MATEMATIKA KELAS IV SDN KEMIJEN 03 SEMARANG - Fatmawati, Sima; Ulia, Nuhyal; Fironika, Rida; Briliyana, Aii Haniyati (Tunas Nusantara, 2024)
ABSTRACTThis research focuses on independent character in mathematics subjects among fourth-grade students at SDN Kemijen 03 Semarang. This research aims to understand how independent character is developed in fourth-grade students, particularly in mathematics. The subjects in this study are the fourth-grade students and teachers. This research is classified as qualitative research using a case study approach. Meanwhile, the data analysis technique uses the Miles and Huberman model with four stages, namely data collection such as observation and interviews, data reduction, data presentation, and conclusion drawing. With triangulation, researchers can test the validity of the data. The results obtained by the researcher indicate that the fourth-grade students exhibit good independent character in mathematics learning in the classroom. The statement is consistent with the results of an interview with the class teacher, who conveyed that most students have already applied independent character during classroom learning. That happened because the teacher had already instilled character in the learning process. The teacher seems to have already implemented contextual, cooperative, and problem-based learning strategies. In addition, the teacher also trains the students to be confident in their abilities. It can be concluded that the role of teachers is very important in instilling independent character in students. The efforts made by the teacher have shown that 80% have been successful in instilling independent character in the students, which is why the fourth-grade students have quite a good independent character.  Keyword: Learning Independence, Mathematical Ability, Development of Independence